FRI0384 IMPACT OF INTERLEUKIN 17 BLOCKING AGENT ON CLINICAL OUTCOME IN SAPHO PATIENTS. (June 2019) - Assmann, Gunter; Thomas Bittenbring, Joerg; Wagner, Annette D.; Schreiber, Martin; Christofyllakis, Konstantinos; Hueffmeier, Ulrike; Pfoehler, Claudia; Neumann, Frank
Abstract : Background: SAPHO syndrome has to be considered as a rare subtype of seronegative spondyloarthritis (SpA) showing typical manifestations with palmoplantar pustolosis and osteitis with hyperostosis; the clinical response of conventional or biological disease modifying drugs (DMARDs) in SAPHO syndrome are often disappointing. Whereas in SpA peripheral arthritis and inflammatory back pain represent the leading symptoms, the SAPHO patients often complain painful osteitis with hyperostosis in the sternal region as well as the palmoplantar pustulosis accompanied by synovitis preferentially in large joints including sacroiliitis. Recently, the detection of higher numbers of CD4+IL17+ lymphocytes in the peripheral blood of SAPHO patients has arisen the hypothesis that Th4/17 helper cells with their secretion of interleukin 17 (IL17) could be involved in the development of inflammation in SAPHO syndrome (1) Objectives: Here we present an observational study of 12 SAPHO patients which were treated with the IL 17 blocking agent secukinumab. In addition, the fraction of CD4/17+ lymphocytes in peripheral blood specimen has been monitored on treatment. Methods: Between January 2015 and February 2017 clinical activity of disease were measured in 37 SAPHO patients with a disease duration of 11 years (median). The disease activity were evaluated by the osteitis score and skin score (ranging from 0 to 6, assessed by physician), the HAQ score (ranging from 0 to 3, assessed by patient), and MRI of the osteitis lesion (activity score 0-3, analogously to 3 domains of OMERACT RAMRIS scoring synovitis, bone marrow edema, and erosions; assessed by radiologist). In this period of time 12 of them showed disease activity due to osteitis and/or skin disease, at which time the treatment of secukinumab at dosage of 300mg as monotherapy has been started, re-evaluated after at least 12 weeks (ranging from 12 to 18 weeks). For monitoring blood specimens were derived to assess the CD4+/IL17+ lymphocyte subpopulation using immunofluorescence technique commercial antibodies for CD4, IL17 (Boehringer Ingelheim, Germany). To analyse the differences between the disease activity scores prior to secukinumab treatment and after treatment we applied the nonparametric analysis according to Wilcoxon test. The p-value < 0.05 was considered as significant. Results: Secukinumab improved osteitis and palmoplantar pustolosis (osteitis score 3.8 to 2.4; p=0.007; PPP 3.4 to 2.4; p=0.071), the HAQ score was reduced from 1.25 to 1.0 (p=0.018), the MRI score from 2.08 to 1.58 (p=0.034). The reduction of at least two clinical activity parameters (osteitis, HAQ and/or MRI) after secukinumab treatment could be documented in all SAPHO patients who showed CD4+IL17+ lymphocytes in higher frequency of 0.4% of leukocytes of peripheral blood. Conclusion: Secukinumab seems to control osteitis and PPP in SAPHO syndrome resulting in reduced burden of disease. High Th17 lymphocytes numbers seems to be associated with higher probability of clinical response to secukinumab. Reference: [1] Firinu D, Barca MP, Lorrai MM, Perra S, Cabras S, Muggianu E, Di Martino ML, Manconi PE, Del Giacco SR. TH17 cells are increased in the peripheral blood of patients with SAPHO syndrome. Autoimmunity. 2014Sep;47(6):389-94 Disclosure of Interests: None declared